INCREASING TEACHERS INQUIRY ABILITY WITH TRAINING INQUIRY ABILITY PROGRAMME AND TEACHING SCIENCE (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2015)
This research aims to produce training program inquiry ability and in teaching science through inquiry approach (is called Program). This study used the methods of research and development. Program design began with a training needs analysis, conducted through field studies and literature, then validated and tested on a limited basis for program design. The implemented programs that have been revised in the main try out in KKGSD Bandar Lampung, by using quasi- experimental design, pretest-posttest control group design. Subjects in this study is the number of elementary school teachers in the city of Bandar Lampung, which involved teachers from primary schools located in the centre of the town, suburb, and remote area in Bandar Lampung. The instrument used was the initial test and final test, questionnaire, assessment of product format, and the observation sheet. The results showed: (1) The inquiry ability of the teacher with PPKIMS through inquiry approach it was higher than with conventional PPKIMS; (2) The inquiry ability of the teacher to teaching with PPKIMS through inquiry approach and conventional PPKIMS after training program was different, and significant improvement towards teachers inquiry ability of PPKIMS through inquiry approach, and it was higher than the conventional PPKIMS.